The Toronto Concussion Study: a prospective investigation of characteristics in a cohort of adults from the general population seeking care following acute concussion, 2016–2020 - Comper, Paul; Foster, Evan; Chandra, Tharshini; Langer, Laura; Wiseman-Hakes, Catherine; Mochizuki, George; Ruttan, Lesley; Lawrence, David W.; Inness, Elizabeth L.; Gladstone, Jonathan; Saverino, Cristina; Tam, Alan; et al. (Frontiers in Neurology, 2023)
Purpose There is limited research regarding the characteristics of those from the general population who seek care following acute concussion. Methods To address this gap, a large cohort of 473 adults diagnosed with an acute concussion (female participants = 287; male participants = 186) was followed using objective measures prospectively over 16 weeks beginning at a mean of 5.1 days post-injury. Results Falls were the most common mechanism of injury (MOI) (n = 137, 29.0%), followed by sports-related recreation (n = 119, 25.2%). Male participants were more likely to be injured playing recreational sports or in a violence-related incident; female participants were more likely to be injured by falling. Post-traumatic amnesia (PTA) was reported by 80 participants (16.9 %), and loss of consciousness (LOC) was reported by 110 (23.3%). In total, 54 participants (11.4%) reported both PTA and LOC. Male participants had significantly higher rates of PTA and LOC after their injury compared to their female counterparts. Higher initial symptom burden was associated with a longer duration of recovery for both male and female participants. Female participants had more symptoms and higher severity of symptoms at presentation compared to male participants. Female participants were identified to have a longer recovery duration, with a mean survival time of 6.50 weeks compared to 5.45 weeks in male participants (p < 0.0001). A relatively high proportion of female and male participants in this study reported premorbid diagnoses of depression and anxiety compared to general population characteristics. Conclusion Although premorbid diagnoses of depression and/or anxiety were associated with higher symptom burden at the initial visit, the duration of symptoms was not directly associated with a pre-injury history of psychological/psychiatric disturbance. This cohort of adults, from the general population, seeking care for their acute concussion attained clinical and functional recovery over a period of 4–12 weeks.